Windowed Fourier transform Java application - Budiman Muhadjir Suryanto (2013)
Fringe analysis is the process of extracting quantitative measurement data from fringe – or line – patterns. It usually consists of phase detection and phase unwrapping. Phase detection is the calculation of the fringe phase from recorded intensity patterns. While phase unwrapping is a method to obtain the clean phase from the said fringe.